Effect of date of planting on the growth and leaf yield of Stevia (Stevia rebaudiana) - Khan, AR; Chowdhury, SH; Karim, MM (Journal of the Bangladesh Agricultural University, 2013)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh from December 2009 to March 2011 to determine the effect of date of planting on growth and leaf yield of Stevia. The experiment comprised 24 dates of planting in the year of 2010 viz. 1 January (T1), 15 January (T2), 1 February (T3), 15 February (T4), 1 March (T5), 15 March (T6), 1 April (T7), 15 April (T8), 1 May (T9), 15 May (T10), 1 June (T11), 15 June (T12), 1 July (T13), 15 July (T14), 1 August (T15), 15 August (T16), 1 September (T17), 15 September (T18), 1 October (T19), 15 October (T20), 1 November (T21), 15 November (T22), 1 December (T23) and 15 December (T24). The experiment was laid out in a Complete Randomized Design with three replications. Twenty four dates of planting were included in the experiment in 72 earthen pots (24 X 3) of 30 cm diameter X 30 cm height. Stem cuttings were placed in shaded seed bed for root initiation. Twenty one - day old stem cuttings were used as planting material. Stem cuttings were transplanted in the pots on the specific dates. Different dates of planting had significant effect on the growth and yield parameters. 1 April 2010 (T7) planting proved to be the superior to the other treatments i.e. plant height (68.50cm), number of leaves plant-1 (142.33), number of primary branches plant-1 (37.33), fresh weight of leaves plant-1 (14.11g), fresh weight of primary and secondary branches plant-1 (11.06g and 20.91g), dry weight of leaves plant-1 (3.38g) which might be due to warm environmental conditions like clear sunshine and high temperature. The overall results suggested that stevia seedlings may be planted from 15 February to 30 April for better yield of leaves. DOI: http://dx.doi.org/10.3329/jbau.v10i2.14684 J. Bangladesh Agril. Univ. 10(2): 205-210, 2012